2018
DOI: 10.12990/mdj.2018.11
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of Prevalence and Characteristics of Pneumatization of Articular Eminence on Cone Beam Computed Tomography

Abstract: Introduction: The aim of this retrospective study was to identify the prevalence and properties of pneumatized articular eminence (PAT) in a group of Turkish population using CBCT.Material and Methods: The subjects for this retrospective study consisted of all 300 adult patients who referred to the Department of Oral Diagnosis and Radiology, Marmara University Faculty of Dentistry, and underwent a single CBCT examination from 2016 to 2017. Age and gender were noted for all patients, and for the cases of pnuema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Şallı et al [15] in their study included 1000 CBCT scans, where PAT was confirmed in 147 individuals and the highest prevalence was in patients between the ages of 30-39. On the other hand, in a study conducted by Borahan et al [ 22] on 300 patients, as many as 103 or 34.3% were over the age of 55. The quoted authors did not clearly demonstrate a relationship between age and the incidence of PAT in the patients studied [1,4,6,[13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Şallı et al [15] in their study included 1000 CBCT scans, where PAT was confirmed in 147 individuals and the highest prevalence was in patients between the ages of 30-39. On the other hand, in a study conducted by Borahan et al [ 22] on 300 patients, as many as 103 or 34.3% were over the age of 55. The quoted authors did not clearly demonstrate a relationship between age and the incidence of PAT in the patients studied [1,4,6,[13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, in a study conducted by Borahan et al [ 22] on 300 patients, as many as 103 or 34.3% were over the age of 55. The quoted authors did not clearly demonstrate a relationship between age and the incidence of PAT in the patients studied [1,4,6,[13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations